2001
DOI: 10.1302/0301-620x.83b4.0830525
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus operative treatment for displaced ankle fractures in patients over 55 years of age

Abstract: Forty-seven patients over the age of 55 years with a displaced fracture of the ankle were entered into a prospective, randomised study in order to compare open reduction and internal fixation with closed treatment in a plaster cast; 36 were reviewed after a mean of 27 months. The outcome was assessed clinically, radiologically and functionally using the Olerud score. The results showed that anatomical reduction was significantly less reliable (p = 0.03) and loss of reduction significantly more common (p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 0 publications
0
52
1
1
Order By: Relevance
“…The OMAS or variations of it have been used in several previous studies. 2,8,9,16,20,23,25 The OMAS was found to correlate significantly (PϽ.05) with several other aspects considered to ''summarize outcome after ankle fracture'' (linear analogue scale, loaded dorsiflexion, presence of osteoarthritis, and anatomical congruence on radiograph). 21 The reliability and responsiveness of the OMAS have not been reported.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The OMAS or variations of it have been used in several previous studies. 2,8,9,16,20,23,25 The OMAS was found to correlate significantly (PϽ.05) with several other aspects considered to ''summarize outcome after ankle fracture'' (linear analogue scale, loaded dorsiflexion, presence of osteoarthritis, and anatomical congruence on radiograph). 21 The reliability and responsiveness of the OMAS have not been reported.…”
Section: Methodsmentioning
confidence: 92%
“…Some studies have compared outcomes of surgically and nonsurgically managed displaced ankle fractures where satisfactory closed reduction was possible. 1,16,22,24 While the results vary, the majority of these studies found better outcomes when surgical fixation was used.…”
Section: Broos and Bisschopmentioning
confidence: 99%
“…Current opinion has increasingly favored primary operative intervention 3 for a displaced or unstable fracture of the ankle, with the greatest emphasis on anatomical reduction and rigid fixation of the lateral malleolus, and fractures of the medial malleolus and those of the posterior malleolus have also been fixed whenever indicated 4,5,6,7,8,9,10,11 In the present series had used both operative and conservative methods for the management of ankle injuries. We had 40 cases in our series of which 32 were operated and 8 treated conservatively with follow up of an average of 11 months with a range of 9 to 15 months.…”
Section: Discussionmentioning
confidence: 98%
“…The most common type of injury was SER (46.6%), followed by pronation-abduction injury (33.3%), and our observation is in accordance with previous reports [12,16,20,22,23] Weber classification that considers integrity of syndesmosis, classifies the ankle fracture into three Groups-A, B, C. In our patients, AO Type B was the most common (66.6%) and least in Type A (6.6%). Motwani et al too report a similar observation [18,22,24].…”
Section: Discussionmentioning
confidence: 67%